STUDY OF THE IMPACT OF FOREIGN INVESTMENT ON ECONOMIC DEVELOPMENT IN EMERGING MARKETS - Spahija, Denis; Li, Wei; Muhammedov, Murod; Nizamov, Akhtam; Iskhakova, Sarvar (LPPM Universitas Jambi, 2025)
In the context of globalisation, national active development is possible by attracting foreign investment and opening joint ventures with foreign partners. Emerging markets need to create a positive business climate and legislation that protects the rights of foreign investors. It is necessary to identify the positive and negative factors that influence foreign investment in the development of countries. The study aimed to address the positive and negative experiences of attracting foreign investment in emerging market economies. The main research method was an analysis of the existing experience of attracting foreign investment in China, Kosovo and Uzbekistan. The study identified positive and negative trends in the inflow and outflow of foreign direct investment (FDI). The degree of influence of the inflow of FDI on the gross domestic product (GDP) and the tendency of its change was determined. Based on the results of the Doing Business rankings, the International Institute for Management Development (IMD) World Digital Competitiveness Index, and the Global Innovation Index, positive and negative trends in attracting foreign investment in the economies of the countries studied were substantiated. The World Digital Competitiveness Ranking includes only 67 countries, including China. Factors that hinder the attraction of foreign investment in China, Kosovo and Uzbekistan were identified. The ways of changing the environment that influence the attraction of foreign investments and the peculiarities of their distribution are substantiated based on the best practices studied.